KOLONISASI FIFA TERHADAP DUNIA: ANALISIS DENGAN PENDEKATAN KRITIS DALAM KOMUNIKASI ORGANISASI - Prastya, Narayana Mahendra (Jurnal Ilmu Komunikasi AKRAB, 2017)
power beyond the country's sovereignty. FIFA will impose sanctions for member states, when the country's government to intervene against football. Instead, FIFA can also press the government of a country to ensure it does not intervene.The majority of the discussion regarding the powers of FIFA more dominant from the perspective of law. This paper offers a conceptual discussion from the viewpoint of science communication. The selected viewpoint is critical approach to organizational communication. Using the concept of Stan Deetz, concluded that what FIFA is a form of colonization of an organization against the parties that are outside the organization. This makes communication patterns FIFA only runs in top down models.Keywords: critical perspectives, FIFA, organizational communication, sport commnication